Validitas Skor Faktor Pola Makan Modern untuk Mengidentifikasi Obesitas pada Pekerja Dewasa di Indonesia - Risti Rosmiati; Hardi Firmansyah (HB PRESS, 2023)
As the prevalence of obesity continues to rise, including in adult workers, workplace-based interventions are needed to promote a healthy diet and prevent obesity. Valid measurement of dietary patterns is necessary to monitor and evaluate the effectiveness of these interventions. Therefore, this study analyzed the validity of the Modern Dietary Pattern Factor Score (MDP-FS) as a proxy indicator of obesity among Indonesian adult workers. This cross-sectional study used the fifth wave of the Indonesia Family Life Survey (IFLS) for sociodemographic, dietary, and anthropometric measures. The receiver operating characteristic (ROC) curve analysis was used to assess the ability of MDP-FS to detect obesity. The Area Under the Curve (AUC) of MDP-FS was 87% (95%CI 86-88.1%). At the MDP-FS cut-off of 5.2, the sensitivity and specificity of MDP-FS to indicate obesity were 74% and 76%, respectively. MDP-FS have good accuracy as a proxy indicator for measuring obesity of adult workers in Indonesia.